Research on network virtualization slicing mechanism in SDN-based testbeds - Jiang LIU; Tao HUANG; Chen ZHANG; Ge ZHANG (Tongxin xuebao)
The researches on future network architecture and key logies need test environment both open and flex-ible. Traditional distribute architecture was short on effective control and new protocol deployment. The emerging of the software defined networking (SDN) technology provides a promising way to s this problem and become a major re-search direction in recent years. In the SDN based network testbed, the virtual network slicing technology was a key issue since it could separate physical resource and provided individual virtual network environment. Therefore, the slicing me-thods of some typical network virtualization platforms with the perspective of “slice identifier”, “virtual nodes ab-straction”and “virtual links abstraction”were introduced , and the future research directions were concluded in this field.